PLIOCENE-LOWER QUATERNARY PLANKTONIC FORAMINIFERAL BIOSTRATIGRAPHY AND PALEOCEANOLOGY ODP HOLE 677A - Bubenshchikova N.V. (My University, 2003)
Planktonic foraminifers from the Pliocene and Lower Quaternary sediments of ODP Hole 677A are thoroughly studied. Many encountered zonal taxa are demonstrated to be the reliable biostratigraphic markers. Planktonic foraminiferal zones PL1b to Pt1 of the Berggren’s scale (Berggren et al. , 1995) are distinguished in the depth interval of 30–210 m in the hole. Changes in planktonic foraminiferal assemblages from the sediments of Site 677A were under influence of the climate-controlled dynamics of surface water masses in the eastern equatorial Pacific during the period from 4.6 to 0.65 Ma. A sharp decrease in abundance of equatorial-tropical species about 3.4 Ma is correlated with termination of the surface water exchange between the Pacific and Atlantic tropical zones owing to the emergence of the Central American land bridge. Surface water temperatures were reconstructed using the method of Barash (1970). The highest temperatures are estimated for the terminal early Pliocene (26.4 ° C) and the late Pliocene (26.6 ° C), and the lowest ones for the initial early Pliocene (18.4 ° C) and the mid-late Pliocene (19.6 ° C). Cold events are recorded in sediments 4.6–4.3, 2.8–2.5, and 1.7– 1.2 Ma old, while periods of 4.3, 4.18–3.4, 2.5–2.3, and 1.0 Ma correspond to the warm ones. In general, the mid-early Pliocene, mid-late Pliocene, and the initial Pleistocene characterize the cold-water conditions, whereas the terminal early and late Pliocene correspond to warm-water environments.
Keywords: planktonic foraminifers; Pliocene–Quaternary sediments; biostratigraphic range; datums; paleoclimatic events; paleotemperatures; Cenozoic::Quaternary; Cenozoic::Neogene::Pliocene; Кайнозой::Четвертичная; Кайнозой::Неоген::Плиоцен